Assessment of advection dispersion through excavation damaged zone in sedimentary rock by in situ tracer tests - TAKEDA, Masaki; ISHII, Eiichi (Journal of Nuclear Fuel Cycle and Environment, 2024)
In rock masses where self-healing is not expected, a highly permeable zone called an excavation damaged zone (EDZ) possibly forms along shafts and tunnels during a facility construction in deep underground. Therefore, understanding nuclide transport characteristics in the EDZ of disposal and access tunnels is an essential issue in the safety assessment of geological disposal of high-level radioactive waste. Tracer tests are effective in evaluating the transport of nuclides in rock masses, but the transport properties of EDZ in sedimentary rock, to our best knowledge, have not been investigated by in situ tracer tests. The authors conducted cross-hole tracer tests on EDZ fractures at the Horonobe Underground Research Laboratory (URL). The tracer tests used two boreholes (H4-1 and P) drilled from one horizontal tunnel to the EDZ that formed above the crown of another tunnel running parallel to the former tunnel at the depth of 350 m in Horonobe URL. The tracer (uranine) injected into the borehole of H4-1 was observed not only in the pumped borehole of P but also in other observation points, whereas we could properly obtain the breakthrough curve under the quasi-steady state injection in the pumped borehole. Based on the breakthrough curve, we performed one-dimensional advection-dispersion analyses, assuming flow path length as a linear distance of 4.2 m between the injection and pumping sections. The results showed the cross-sectional area of flow path and the mean velocity to be 5.2×10-3 m2 and 2.3×10-4 m/min, respectively, and the longitudinal dispersivity was estimated to be 0.12 m to the flow path length of 4.2 m. Assuming the flow path to be tortuous in the EDZ fracture network further reduces the estimated cross-sectional area. The longitudinal dispersivity normalized to the assumed flow path length was 3% and consistent with the empirical relationship between flow path length and longitudinal dispersivity for natural fractures and rock matrices in the literature. The series of tracer tests and analyses applied in this study demonstrated that the effects of dispersion can be expected also within EDZ fractures, similar to the level in natural fractures and rock matrices.